Overcoming tetracycline pollution in soils through the addition of a mycorrhizal fungal species Funnelifonni.s mosseae - Yang, Chao; Baiyan Cai; Chong, Harry Lye Hin; Li, Linghui; Yong, Jean Wan Hong; Chong, Khim Phin (Elsevier Inc., 2025)
The presence of residual antibiotics in the black soils of northeastem China poses a significant threat to food safety. This study investigated the potential of Funnelifonnis mosseae, one of the predominant biocontrol fungi in northeastemC hina, to mitigate the negative effects of tetracycline contamination ( 40 mg kg-1) in soil. Advanced biotechnological methods were employed to assess plant growth, soil microbial antioxidant enzyme activity, and soil fertility. Additionally, changes in microbial diversity, composition, and abundance at both the phylum and genus levels were analyzed through high-throughput sequencing of the 16S rRNA and ITS gene regions of soil microorganisms. The results demonstrated that F. mosseae colonization in tetracycline-contaminated soils significantly improved soybean growth. Enhanced antioxidant enzyme activity in the soybean plants further contributed to increased resistance against tetracycline stress. Notably, F. mosseae colonization was associated with lower tetracycline levels, elevated total nitrogen (TN) content in the soil, alongside a shift in microbial diversity and abundance favoring nitrogen-fixing bacteria.T his indicated that F. mosseae colonization influenced the bacterial and fungal community composition, altering the relative abundance of dominant microbial taxa and modulating the overall soil microenvironment. In conclusion, the application of F. mosseae effectively mitigated tetracycline-induced stress, improved soil health, and provided a promising strategy for the bioremediation of antibiotic-contaminated agricultural soils.